The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcell.2022.821014
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload Induces Oxidative Stress, Cell Cycle Arrest and Apoptosis in Chondrocytes

Abstract: Clinical and experimental evidence point to the presence of considerable links between arthropathy, osteoarthritis (OA) in particular, and iron overload possibly due to oxidative stress and tissue damage. However, the specific cellular targets of iron overload-related oxidative stress in OA remain ambiguous. We examined the effects of iron overload on chondrocyte health using the C-20/A4 chondrocyte cell line. Cells were treated with increasing concentrations of ferric ammonium citrate (FAC) to mimic iron over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…FTH1 plays an anti-cancer role by promoting angiogenesis ( 39 , 40 ). Increased expression of FTH1 inhibits cancer by promoting apoptosis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…FTH1 plays an anti-cancer role by promoting angiogenesis ( 39 , 40 ). Increased expression of FTH1 inhibits cancer by promoting apoptosis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor β 1 can protect chondrocytes from oxidative stress by regulating autophagy (Kurakazu et al, 2021). Karim et al found that iron overload in chondrocytes can induce oxidative stress, cell cycle arrest and apoptosis (Karim et al, 2022). Pang et al found that Bardoxolonemethyl can inhibit chondrocyte apoptosis and ECM degradation induced by oxidative stress in vitro, and reduce OA in vivo (Pang et al, 2021).…”
Section: How To Solve the Oxidative Stress In Knee Osteoarthritismentioning
confidence: 99%
“…Iron overload is typically detected by measuring serum transferrin saturation (the amount of ferric iron bound to the carrier protein transferrin in the circulation; >45 percent indicates iron excess) in conjunction with serum ferritin concentration ( 35 ). Iron overload has been shown to hasten bone loss in healthy postmenopausal women and middle-aged men, increase apoptosis, and impair chondrocyte functional competence ( 38 , 39 ). Furthermore, aberrant iron accumulation causes nerve injury in rats by up-regulating CXCL10/CXCR3 signaling in the spinal dorsal horn, resulting in mechanical allodynia and thermal hyperalgesia ( 40 ).…”
Section: Discussionmentioning
confidence: 99%